PENGARUH MODEL PEMBELAJARAN RADEC TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN SEJARAH KELAS X MAS ASSALAM NAGA BERALIH - Husnah Mukhlis, Nikmatul; Bunari; Asril (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the influence of the RADEC learning model (Read-Answer-Discuss-Explain-Create) on students' critical thinking skills in history learning for class X at MAS Assalam Naga Beralih. This study uses a quantitative approach with a quasi-experimental method and experimental design. control group Pre-test-Post-test design. The research sample consisted of class X D as an experimental class using the RADEC model and class X A as a control class using the RADEC model.Problem Based Learning (PBL). Data was collected through a critical thinking ability test in the form ofpre-test And post-test. The results of the hypothesis test usingIndependent Samples t-testshows a significance value (Sig. 2-tailed) of 0.000 < 0.05. Based on the testing criteria, Ha is accepted and Ho is rejected, which proves that there is a significant influence of the use of the RADEC learning model on students' critical thinking skills. The increase in critical thinking skills can be seen from the average valuepost-testThe experimental class achieved a score of 88.27, significantly higher than the control class's score of 67.50. The N-Gain test results in the experimental class indicated that the increase in critical thinking skills was in the high category and was deemed effective in enhancing critical thinking. Thus, the systematic application of the RADEC learning model has proven effective in triggering higher-level cognitive processes and enhancing students' critical thinking skills in history learning.